2004
DOI: 10.1111/j.1559-1816.2004.tb02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Perceived Justice as Predictors of Survivors’ Reactions Following Downsizing1

Abstract: Downsizing, when deemed unfair, can result in negative outcomes in terras of survivors’ job attitudes and behaviors. Little research to date has examined whether a survivor's personality moderates these reactions. The present study examines the roles of personality and organizational justice in survivors’ reactions to downsizing. Results show that angry hostility moderates the relationships between survivors’ perceived interactional justice and (a) their organizational commitment, and (b) their intention to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 61 publications
1
30
0
4
Order By: Relevance
“…Organizational managers might not consider the impact of organizational changes on morale, productivity (Cascio et al, 1997) and satisfaction (Wah, 1999) of employees because their future predictions are based solely on beliefs or past experiences (Kotter and Schlesinger, 2008). This planning error in the change process has serious consequences for the organization, such as desertion (Brennan and Skarlicki, 2004) or absenteeism (Martin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Organizational managers might not consider the impact of organizational changes on morale, productivity (Cascio et al, 1997) and satisfaction (Wah, 1999) of employees because their future predictions are based solely on beliefs or past experiences (Kotter and Schlesinger, 2008). This planning error in the change process has serious consequences for the organization, such as desertion (Brennan and Skarlicki, 2004) or absenteeism (Martin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that cynicism about organizational change can arise from previously failed change initiatives (Connell & Waring, 2002;Reichers et al, 1997;Abraham, 2000), or where change outcomes are unfavourable (Oreg, 2006) and injustice is perceived (Chawla & Kelloway, 2004;Brennan & Skarlicki, 2004;Oreg, 2006). This can lead to resistance to change or at least lack of engagement in it (Reichers et al, 1997;Connell & Waring, 2002;Stanley et al, 2005).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Past research has identified the impact of personality in perceptions of justice (e.g. Colquitt et al, 2006;Lilly & Virick, 2006), and specifically in the context of change (Brennan & Skarlicki, 2004;Moon et al, 2008). Elsewhere in our interviews in the broader study of emotions and change, respondents made comments about various experiences of fairness and unfairness and how they triggered affective responses.…”
Section: Limitations Of Research Study and Future Directionsmentioning
confidence: 98%
See 2 more Smart Citations